Exploring colloquial English proficiency in Azerbaijani secondary schools - Huseynzade, Aytan (Educational Challenges, 2025)
Purpose. Expertise in colloquial English is important for effective communication, and it has become increasingly important in our rapidly changing world. This article examines how Azerbaijani secondary schools teach colloquial English and focuses on the differences between private and public institutions.Methodology. This study employed a comparative analysis, integrating both qualitative and quantitative research methods. Data collection involved a combination of approaches, including interviews, observations, surveys, and demographic analysis, to provide a comprehensive understanding of the subject matter.Results. Educators confront difficulties when teaching colloquial English. This study’s findings improve the discussion about language expertise in non-native English-speaking situations and provide useful recommendations for improving language teaching methods in Azerbaijan. Conclusions. This article shows how to improve language education for many Azerbaijani students while meeting global communication standards.
Keywords: Azerbaijani secondary schools; Colloquial English; comparative analysis; language proficiency; language teaching; private vs. public schools